Branching Pattern of Coronary Arteries in Prenatal Heart of Buffalo (Bubalus bubalis) - Gupta, Anuradha; Bansal, Neelam (Indian Journal of Veterinary Anatomy, 2012)
The present investigation revealed that the left and right coronary arteries of buffalo foetii arose from the left caudal and right caudal aortic sinuses, respectively. After coursing a short distance under left auricle, the left coronary artery was divided into paraconal inter-ventricular artery and circumflex branch. Paraconal inter-ventricular branch ran in the left longitudinal groove and before reaching the apex it curved upward and anastomosed with the continuation of circumflex branch in the right longitudinal groove. The circumflex branchran in the coronary groove caudally and gave intermediate branch on posterior border and later continued in right longitudinal groove to anastomose with the continuation of paraconal inter-ventricular branch. Right coronary artery passed under the right auricle and divided into 2 main branches. One branch anastomosed with the circumflex branch of the left coronary artery in the coronary groove and the second one was septal artery and supplied the inter-ventricular septum.